HUMAN RESOURCE MANAGEMENT IN ISLAMIC SCHOOLS: MANAJEMEN SUMBER DAYA MANUSIA DI SEKOLAH ISLAM - Fajriyah, Aulia'ul; Rindaningsih, Ida (Antis Publisher, 2024)
The purpose of this research is to provide feedback to improve work performance and self-development in educating at Islamic schools. The career development and promotion system is implemented to improve employee skills and achievements so that they can increase self-improvement within an Islamic school institution. This research method is based on library research and collected from various written sources, including magazines, scientific publications, journals and other sources relevant to the research discussed by the author. The research results state that qualifications, recruitment strategies, staff orientation, salary policies, employee regulations, coaching and development, employee evaluation, employee careers and ranks, and welfare are just some of the tasks that make up human resource management in Islamic schools. As well as employee coaching and development is carried out to improve Islamic understanding, personality, pedagogical, professional and social competencies. And employee performance evaluation is carried out based on individual achievements and participation in Islamic school activities so that each educator or teacher can develop and increase the potential of human resources in Islamic school institutions.